Polymorphism of the Klotho G-395a Gene Promoter with the Incidence of Preeclampsia - Desi Arlindia; Mgs. Irsan Saleh; Zen Hafyy; Legiran; Erial Bahar; Kms. Yusuf Effendi; Ferry Yusrizal (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
A B S T R A C TIntroduction. Preeclampsia is one of the leading causes of maternal and perinatalmorbidity and mortality and is still a disease of theory. Klotho is a new gene, inseveral biological processes in the pathophysiology of preeclampsia that play a rolein regulating endothelial nitric oxide production, angiogenesis, production ofantioxidant enzymes and protection against endothelial dysfunction. The Klotho G-395A genotype AA promoter polymorphism is the cause of hypertension. This studyaims to determine the relationship of the Klotho G-395A promoter polymorphism tothe incidence of preeclampsia. Methods. This study is an analytical study with acase-control design. The research was conducted at Pembina community healthcentre of Palembang and the public hospital of Prabumulih in February - July 2020and involving 50 case group and 50 control group. To determine the genotype andallotype of the Klotho G-395A gene promoter polymorphism, using polymerase chainreaction examination. Result. The results showed that the risk factors for maternalage and maternal gestational age had a significant relationship with the incidence ofpreeclampsia (p-value 0.015; p-value 0.000). There was a significant relationshipbetween the Klotho G-395A genotype GA + AA promoter polymorphism and theincidence of preeclampsia (p-value 0.024; OR = 2.571; 95% CI = 1.122-5.895), whileallotypes in the study sample also had a significant relationship with the incidenceof preeclampsia. preeclampsia (p-value 0.025; OR = 1.978; 95% CI = 1.087-3.599).Conclusion: There is a significant relationship between the Klotho G-395A genepromoter polymorphism and the incidence of preeclampsia.